Implementation of Automated Intelligent Irrigation and Fertilization System Based on the Internet of Things for Home Wine Hobbyists - Muh. Azfa Azra; Jumadi M. Parenreng; Mustari S Lamada; M. Syahid Nur Wahid; Abdul Wahid (Program Studi Teknik Komputer, 2025)
The agricultural sector faces serious challenges due to climate change and rising global food needs, which demand more efficient implementation of water and plant nutrient management. Viticulture, particularly on an urban scale, requires precise irrigation and fertilization arrangements because grapes are very sensitive to water availability and nutrient concentrations at certain growth phases. This research aims to design and implement a prototype of an Internet of Things (IoT)-based Smart Nutrition Irrigation System for home wine hobbyists using the Research and Development (R&D) method. The developed system is able to monitor environmental and soil conditions in real-time and control irrigation and fertilization automatically based on predetermined parameters. The results of the performance evaluation showed that the system had an average response time of ±1–3 seconds from the time the sensor data was received until the actuator was activated. TDS sensors are able to detect changes in the concentration of fertilizer solutions in the range of 0–1200 ppm, thus supporting the quality control of nutrient solutions. The results of functional tests show that the system successfully activates irrigation automatically when soil moisture is below the 75% threshold and runs scheduled fertilization consistently. In addition, the system is able to send real-time monitoring and actuator status notifications through an online application with a 100% message success rate during testing. Overall, the system has been shown to improve the efficiency of water and nutrient management in urban grape cultivation and has the potential to be further developed on a larger scale and applied to precision agriculture